2009
DOI: 10.1158/1541-7786.mcr-08-0568
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Related Protein Regulates Cell Survival Pathways via Integrin α6β4-Mediated Activation of Phosphatidylinositol 3-Kinase/Akt Signaling

Abstract: Parathyroid hormone-related protein (PTHrP) is expressed by human prostatic tissues and cancer cell lines. PTHrP enhances tumor cell growth and metastasis in vivo and up-regulates proinvasive integrin α 6 β 4 expression in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 52 publications
(83 reference statements)
3
36
0
Order By: Relevance
“…Similar results were reported by Falzon and collaborators [44] in a study on human prostate cancer cell lines. It is known that prostate carcinogenesis is characterized by the increase of PTHrP secretion [45] which was proven to up-regulate integrin α6β4, capable to activate the PI3K pathway when signaling synergistically with growth factor receptors such as ErbB2, ErbB3, and c-Met.…”
Section: Pthrp As a Stimulator Of Cell Survival And Proliferation Ofsupporting
confidence: 91%
“…Similar results were reported by Falzon and collaborators [44] in a study on human prostate cancer cell lines. It is known that prostate carcinogenesis is characterized by the increase of PTHrP secretion [45] which was proven to up-regulate integrin α6β4, capable to activate the PI3K pathway when signaling synergistically with growth factor receptors such as ErbB2, ErbB3, and c-Met.…”
Section: Pthrp As a Stimulator Of Cell Survival And Proliferation Ofsupporting
confidence: 91%
“…Notably, this was the first time that PI3K had been implicated in carcinoma invasion. This finding was subsequently confirmed in a number of additional reports (3941), although the exact mechanism by which integrin α6β4 activates PI3K initially remained elusive. The cytoplasmic domain of the integrin β4 subunit does not contain a consensus-binding motif for the regulatory subunit of PI3K, making direct activation of this pathway by integrin β4 subunit unlikely (4, 6, 42).…”
Section: Integrin α6β4 Signaling In Malignant Cellsmentioning
confidence: 66%
“…If anchorage to the ECM is lost, the subsequent loss of integrin signaling can inhibit cell growth and promote a specialized form of apoptosis referred to as anoikis (63). While tumor suppressive functions of the integrin β4 subunit have been identified in bladder (64), colon (65), and breast carcinoma (66) cell lines, a number of additional studies have indicated that the β4 integrin promotes cell survival (19, 41, 66–68). This dichotomy appears to hinge on the expression and mutation status of the p53 tumor suppressor.…”
Section: Integrin α6β4 Signaling In Malignant Cellsmentioning
confidence: 99%
“…PTHLH interacts with parathyroid hormone/parathyroid hormone-related protein receptor (PTH/PTHLH type 1 receptor, PTH1R), a member of family B G-protein coupled receptor, and controls several cellular function through activation of the cAMP/PKA or IP 3 /PKC signaling cascades. PTHLH promotes cell proliferation, migration, and invasion, and prevents apoptosis in different types of cancers91011. In HNSCC, PTHLH has been reported as a poor prognostic marker and is stimulated in vitro cell growth through promoting cell cycle progression12.…”
mentioning
confidence: 99%